PENGARUH DIKLAT DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT SYNERGIS GLOBAL PERFORMA - Gaylah Hanifah; Nuridin (Jurnal Manajemen Bisnis Krisnadwipayana, 2017)
The purpose of this research was to determine the influence both individually and jointly, variable of training and motivation to variable of employees’ performance at PT. Synergis Global Performa. Method of collecting data through primary data. Method of Data Analysis WITH using regression, correlation, determination both jointly and individually, then continued by hypotheses test. But before it was analyzed, first was done the test of data instrument. The results of research showed that: From the result of analysis about the factors which is affecting the performance of employees, it appears that these two variables were analyzed, namely training and motivation, so the most dominant to influence employees' performance is training variable. That was proved by the result from the calculation of t count for each variable, where t count of training (12.246) is greater than the value of the t count of motivation (4,003).